Understanding the Intention of Using Mobile Social Networking Apps Across Cultures. Issue 12 (2nd December 2018) - Qin, Li; Kim, Yongbeom; Tan, Xin
ABSTRACT: Understanding the user acceptance of mobile social networking apps in different cultures can provide powerful insights for managers and marketers of social networking apps to develop effective globalized and localized strategies to attract users worldwide. Following the theory of planned behavior, this study develops a research model of privacy concern (PC), privacy risk (PR), and perceived enjoyment (PE) as attitudinal beliefs, subjective norm (SN) as normative belief, and smartphone self-efficacy (SE) as control belief to understand users' intention to use mobile social networking apps. In particular, the impact of culture was investigated, considering the user base of mobile social networking apps is distributed globally and culturally diversified, and cultural values have direct impact on behavior. The research model was validated by survey data collected from 151 participants in the U.S. and 170 participants in South Korea. The data analysis results show that perceived enjoyment and subjective norm are the most important drivers behind users' intention to use mobile social networking apps for both countries. No significant difference was found for the effects of privacy risk and subjective norm upon users' intention to use mobile social networking apps across cultures. Implications of the findings upon theory and practice are discussed.